Functional analysis of a new splicing mutation in the MYBPC3 gene in hypertrophic cardiomyopathy - R. R. Salakhov; M. V. Golubenko; M. Y. Skoblov; R. R. Savchenko; N. R. Valiakhmetov; E. N. Pavlyukova; M. S. Nazarenko (Бюллетень сибирской медицины, 2024)
Aim. To study the pathogenic effect in the MYBPC3 splice-site variant in the patient with hypertrophic cardiomyopathy. Materials and methods. The study was conducted using a DNA sample obtained from a patient with hypertrophic cardiomyopathy, in whom a previously undescribed variant was identified in the splice donor site of intron 21. The methods used included constructing and cloning of minigenes (vector pSpl3-Flu2-TKdel) and transfection of a human cell culture (HEK293T), followed by isolation of mRNA, production of cDNA, PCR of the minigene region containing the analyzed fragment, agarose gel electrophoresis, and Sanger sequencing. Results. The chr11:47339649-A-C (hg38) variant, disrupting the splice donor site in intron 21 (NM_000256.3: c.2067+2T>G), was identified in the 23-year-old patient with obstructive hypertrophic cardiomyopathy. To directly analyze the effect of this variant on splicing, a vector containing exon 21, intron 21, exon 22, and partially introns 20 and 22 of the MYBPC3 gene was obtained. A comparison of mRNAs from the minigenes containing / not containing the variant showed that the chr11:47339649-A-C substitution led to exon 21 and exon 22 skipping during splicing. Conclusion. The study established the functional significance of the previously undescribed variant c.2067+2T>G in the MYBPC3 gene, resulting in disruption of the mRNA splicing mechanism in the patient with hypertrophic cardiomyopathy. This variant can be classified as pathogenic.